On the points of failure and entry in global food systems - Ulimwengu, John M. (International Food Policy Research Institute, 2025)
This study develops a dual-framework for identifying points of failure (PFs) and points of entry (PEs) in global food systems. Building on Schneider et al. (2025), we extend their entry-point analysis by introducing PFs—nodes where systemic risk concentrates. Using dynamic systems modeling and directed network analysis of 50 indicators from the Food Systems Countdown Initiative, we derive PF and PE indexes based on structural metrics from the adjacency matrix. While empirically grounded in network topology, the model accommodates behavioral lags and policy sensitivity. Findings reveal that high-risk and high-leverage components often overlap, enabling more strategic and adaptive interventions. Designing interventions without understanding fragility would be akin to engineering a machine for acceleration while ignoring its weakest links.